Tricuspid and mitral remodelling in atrial fibrillation: a three-dimensional echocardiographic study. (4th March 2022) - Ortiz-Leon, Xochitl A; Posada-Martinez, Edith L; Trejo-Paredes, Maria C; Ivey-Miranda, Juan B; Pereira, Jason; Crandall, Ian; DaSilva, Paul; Bouman, Eileen; Brooks, Alyssa; Gerardi, Christine; Houle, Helene; Hur, David J; et al.
Abstract: Aims: Atrial fibrillation (AF) is associated with atrial enlargement, mitral annulus (MA) and tricuspid annulus (TA) dilation, and atrial functional regurgitation (AFR). However, less is known about the impact of AF on both atrioventricular valves in those with normal and abnormal ventricular function. We aimed to compare the remodelling of the TA and MA in patients with non-valvular AF without significant AFR. Methods and results: Ninety-two patients referred for transoesophageal echocardiography were included and categorized into three groups: (i) AF with normal left ventricular (LV) function (Normal LV-AF), n = 36; (ii) AF with LV systolic dysfunction (LVSD-AF), n = 29; and (iii) Controls in sinus rhythm, n = 27. Three-dimensional MA and TA geometry were analysed using automated software. In patients with AF regardless of LV function, the MA and TA areas were larger compared with controls (LVSD-AF vs. Normal LV-AF vs. Controls, end-systolic MA: 5.2 ± 1.1 vs. 4.5 ± 0.7 vs. 3.9 ± 0.7 cm 2 /m 2 ; end-systolic TA: 5.6 ± 1.3 vs. 5.3 ± 1.3 vs. 4.1 ± 0.7 cm 2/ m 2 ; P < 0.05 for each comparison with Controls). TA and MA areas were not statistically different between the two AF groups. The TA increase over controls was greater than that of the MA in the Normal LV-AF group (27.7% vs. 15.6%, P = 0.041). Conversely, in the LVSD-AF group, MA and TA increased similarly (35.9% vs. 32.4%, P = 0.660). Conclusion: Patients with AF showed dilation of both TA and MA compared with patients in sinus rhythm. In patients with normal LV function, AF was associated with greater TA dilation than MA dilation whereas in patients with LVSD the TA and MA were equally dilated. Graphical Abstract: